Roadmap assessment of phonological awareness (RACF). (2010)
This paper aimed at assessing phonological awareness in elementary school children, in order to examine criterion validity evidences through comparing grades, and also to identify differences related to gender and age. Participants were 221 children aged 6 to 12 years (M=8.53; SD=1.40), who individually responded to Roteiro de Avaliação da Consciência Fonológica (RACF), a screening instrument. Out of 15 possible scores, children scored an average of 11.23 (SD=2.60), finding greater difficulty in identifying intermediate sounds of words. The ANOVA indicated significant differences between grades [F(3,218)=18,66; p<0,001], with higher scoring for students in more advanced levels, which constitutes evidence of criterion validity for the instrument. The average scores of boys and girls were not significantly different, and in relation to age, older children had higher averages. It is suggested that further studies are conducted with larger and varied samples, as a way to also allow comparison with other potentially relevant variables.